Laser Space Communications. - Aviv, David G. (Artech House Space Technology and Applications., 2006)
Laser space communications is a hot topic among electrical engineers working for the government and in the defense industry, and this groundbreaking resource is the first to offer professionals a thorough, practical treatment of the subject. The book focuses on the feasibility of laser space communications between satellites, satellites and airborne platforms, and satellites and ground based stations to achieve worldwide connectivity. It covers all the critical topics that engineers working in the field need to understand such as weather avoidance, 5th Generation Internet (5-GENIN), and noise.